Destination Image Influencing to Revisiting Intention of Chinese Tourists Travelling in Phuket: ภาพลักษณ์แหล่งท่องเที่ยวที่ส่งผลต่อความตั้งใจเดินทางกลับมาเที่ยวซ้ำ ของนักท่องเที่ยวชาวจีนที่เดินทางมาท่องเที่ยวภูเก็ต - Soonsan, Nimit; Somkai, Umaporn (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ วัตถุประสงค์ของการศึกษาครั้งนี้คือ การตรวจสอบอิทธิพลระหว่างภาพลักษณ์แหล่งท่องเที่ยวการรับรู้คุณค่า ความพึงพอใจและความตั้งใจเดินทางกลับมาเที่ยวซ้ำ การศึกษาครั้งนี้ใช้วิธีวิจัยเชิงปริมาณโดยเก็บข้อมูลด้วยแบบสอบถามจากนักท่องเที่ยวชาวจีนในจังหวัดภูเก็ตจำนวน 342 คน แล้วจึงวิเคราะห์ผลด้วยโมเดลสมการโครงสร้างเพื่อทดสอบความสัมพันธ์เชิงสาเหตุ ผลการศึกษาแสดงให้เห็นว่าภาพลักษณ์แหล่งท่องเที่ยวมีอิทธิพลต่อการรับรู้คุณค่า แต่ภาพลักษณ์แหล่งท่องเที่ยวไม่มีอิทธิพลต่อความพึงพอใจนักท่องเที่ยว ส่วนการรับรู้คุณค่ามีอิทธิพลต่อความพึงพอใจนักท่องเที่ยว นอกจากนั้นความพึงพอใจนักท่องเที่ยวมีอิทธิพลต่อความตั้งใจเดินทางกลับมาเที่ยวซ้ำ ABSTRACT This study aimed to examine the influence among destination image, perceived value, satisfaction, and revisiting. The quantitative method was used in this study. A total of 342 questionnaires were collected from Chinese tourists in Phuket. Moreover, structural equation modelling was used for testing the causal relationship. The result indicated that destination image had impact on perceived value but it showed that no direct influence on tourist satisfaction. Moreover, perceived value influenced on tourists’ satisfaction. In addition, tourists’ satisfaction impacted on revisiting intention.